Development of a Productivity Assessment Tool for Hospital Settings in Iran: A Delphi Study - Somayeh Mahdiyan; Mosuod Ferdosi; Sima Rafiei; Rooholah Askari (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Measurement of the organizational performance would be effective and helpful for improvement, in the case that it is based on an appropriate and principled system. Such a system uses specific indicators to measure the productivity and performance of the organizations. In fact, these indicators act as useful tools for strategic planning in managerial levels. Given the importance of the issue, this study aimed to develop the key productivity indicators for hospitals affiliated to Isfahan University of Medical Sciences. These indicators are designed to be applied in evaluation, implementation, and improvement processes of the organizations under study. Methods: This was a qualitative study conducted among the hospitals affiliated to Isfahan University of Medical Sciences in 2015. Purposive sampling method was applied and the study participants were selected through snowballing. Then, the participants were organized in a focus group consisting of 16 experts in the field of hospital performance and efficiency indicators to achieve the research objectives by using indexing matrix method. Finally, validity of the developed indices was confirmed using Delphi method. Results: A total of 42 productivity indicators were formulated. Of these, nine indices were input (structural), which included financial, human resources, and energy consumption indicators. The next 29 indices were output and mainly belonged to the financial, efficiency, and quality area. The final four indices included process indicators and consisted of length of stay in emergency department, waiting time for out of hospital counseling, and waiting time for the presence of resuscitation team at the patient bedside during the cardiopulmonary resuscitation. Conclusion: Development of the indicators in three areas of input, process, and output helped managers and policy makers to access reliable and valid instrument for measuring organizational productivity.